Carbon for Micro and Nano Devices - Sharma, Swati (Berlin : Walter De Gruyter, 2024)
Micro and nano devices are an integral part of modern technology. To address the requirements of the state-of-the-art technology, topics are selected from both chip-based and flexible electronics. A wide range of carbon materials including graphene, carbon nanotube, glass-like carbon, porous carbon, carbon black, graphite, carbon nanofiber, laser-patterned carbon and heteroatom containing carbon are covered. This goal is to elucidate fundamental carbon material science along with compatible micro- and nanofabrication techniques. Real-life example of sensors, energy storage and generation devices, MEMS, NEMS and implantable bioelectronics enable visualization of the outcome of described processes.
Included bibliography and index
Keywords: Carbon electronics; Carbon nanostructures; Microdevices; Laser patterning